Impact of Digital Marketing as a Tool of Marketing Communication: A Behavioral Perspective on Consumers of Bangladesh - Yamin, Ahmad Bin (American Journal of Trade and Policy, 2017)
This study shows the impact of digital marketing on behavioral prospect of consumers of Bangladesh. For conducting this study a sample of Bangladeshi consumers are surveyed to attain their behavioral pattern on digital marketing. Modern day marketing has been going through a radical change. Fast moving marketing trends based on the growth and innovation of new technologies as well as portable communication devices influencing the customer behavior significantly. A well designed marketing plan with specific digital marketing tools is the demand in the integrated marketing communication plan for this tech friendly environment. High speed internet connectivity brings massive number of young crowd in social media indicating marketer should be more focused and concentrated in digital marketing tools for effective and efficient targeting of market as well as to achieve other organizational goals.